The New Women's Perceptions of Missionary Women in Late Qing Dynasty in The Christian Home in China - GUO, Hong; WU, Yanru (Journal of Research for Christianity in China (JRCC), 2026)
Missionary women who came to China during the late Qing primarily focused their work on Chinese women. Coming from Western and religious backgrounds, yet also being long influenced by Chinese culture, their understanding of Chinese women’s present situation and future was both contradictory and, at times, reconciled. Around the time of the Boxer Movement, ideas of gender equality and women’s rights gradually became new aspirations for Chinese women. missionary women did not overlook these social changes. When revising the second edition of The Christian Home in China: The Daughter in The Home, a textbook for girls in missionary schools, they adopted a framework centered on moral cultivation, love for family, love for country, and love for the Kingdom of Heaven. Through discussions on law, women’s rights, equality, and freedom, they sought to guide female believers into the currents of societal transformation. At the same time, influenced by both Christian family values and traditional Chinese culture, The Daughter in The Home also exhibited clear characteristics of the “virtuous wife and good mother” ideology.
Keywords: The Christian Home in China: The Daughter in The Home, Missionary women, Chinese women